Recent Advances in Three-Dimensional Stem Cell Culture Systems and Applications. (11th October 2021) - Wu, Xiaowen; Su, Junxiang; Wei, Jizhen; Jiang, Nan; Ge, Xuejun
Abstract : Cell culture is one of the most core and fundamental techniques employed in the fields of biology and medicine. At present, although the two-dimensional cell culture method is commonly used in vitro, it is quite different from the cell growth microenvironment in vivo. In recent years, the limitations of two-dimensional culture and the advantages of three-dimensional culture have increasingly attracted more and more attentions. Compared to two-dimensional culture, three-dimensional culture system is better to realistically simulate the local microenvironment of cells, promote the exchange of information among cells and the extracellular matrix (ECM), and retain the original biological characteristics of stem cells. In this review, we first present three-dimensional cell culture methods from two aspects: a scaffold-free culture system and a scaffold-based culture system. The culture method and cell characterizations will be summarized. Then the application of three-dimensional cell culture system is further explored, such as in the fields of drug screening, organoids and assembloids. Finally, the directions for future research of three-dimensional cell culture are stated briefly.